Is extermination to be the legacy of Mary Gilbert's cat?. (May 2016) - Hillier, Jean; Byrne, Jason
Once imported to Australia as rodent controllers, cats are now regarded as responsible for a second wave of mammal extinction across the continent. Utilising the Foucauldian concept of biopolitics, we investigate critically the institutional field of cat regulation in Australia, exemplified by the Western Australian Cat Act 2011 and the Federal Environment Minister's 10-year campaign to eradicate feral cats. Analysis of the biopolitical dispositif of ferality, and its elements of knowledge, subjectivation and objectivation and power processes, illustrates the dispositions through which what might be regarded as felicide has become organisational practice. We propose alternative practices emphasising the productive potentialities of biopolitics.